2006
DOI: 10.3989/scimar.2006.70n3423
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in size at onset of maturity of female southern rock lobster <i>Jasus edwardsii</i> around Tasmania, Australia

Abstract: SUMMARY:The size at onset of maturity (SOM) of female Jasus edwardsii (Hutton, 1875) was estimated at 50 sites around Tasmania, Australia, based on the presence of ovigerous setae. There was a distinct spatial cline with the largest SOM being found at northwestern sites and the smallest at southwestern sites. Variation in SOM between sites was substantial and ranged from 59 mm to 112 mm carapace length. The observed decline in SOM from north to south was the reverse of that described for the same species at si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 27 publications
(20 reference statements)
2
34
0
1
Order By: Relevance
“…For example, egg-bearing lobsters as small as 53-mm CL have been reported off San Diego in the South region (Hovel and Neilson 2011;Hovel et al 2015), while the smallest SAM reported in the North Coast region (Palos Verdes) was about 63 mm (Lindbergh 1955). The variation in SAM may be due to differences in temperature, as numerous studies of other lobster, including spiny lobster, have documented an earlier onset of maturity in warmwater areas (Templeman 1936;Annala et al 1980;Little and Watson 2005;Gardner et al 2006). Unlike in the South, our calculations based on the CASP data suggest that egg production in the Northwest Islands is greatest in the legal fraction of the population, which is vulnerable to fishing and thus at greater risk of reduction in egg production.…”
Section: Regional Catch Characteristicsmentioning
confidence: 69%
“…For example, egg-bearing lobsters as small as 53-mm CL have been reported off San Diego in the South region (Hovel and Neilson 2011;Hovel et al 2015), while the smallest SAM reported in the North Coast region (Palos Verdes) was about 63 mm (Lindbergh 1955). The variation in SAM may be due to differences in temperature, as numerous studies of other lobster, including spiny lobster, have documented an earlier onset of maturity in warmwater areas (Templeman 1936;Annala et al 1980;Little and Watson 2005;Gardner et al 2006). Unlike in the South, our calculations based on the CASP data suggest that egg production in the Northwest Islands is greatest in the legal fraction of the population, which is vulnerable to fishing and thus at greater risk of reduction in egg production.…”
Section: Regional Catch Characteristicsmentioning
confidence: 69%
“…The rapidity in depth transition in shell colour was variable between regions and around Tasmania, but had a weak latitudinal trend, in a similar pattern to that which occurs with depth range of red lobsters' growth rates and size at onset of female maturity across this region (McGarvey et al 1999;Gardner et al 2006). The latter is thought to be driven by differences in temperature, whereas the strong relationship we document between red shell coloration and depth appears to have a dietary basis, presumably because of changes in reef composition and in prey items with depth.…”
Section: Spatial Variation In Colourmentioning
confidence: 76%
“…For example, growth of 100 mm CL females varies from 1 mm per annum in the southwest to 14 mm per annum in the northwest . Likewise, the size at onset of maturity roughly doubles across a similar spatial range from 59 mm CL in the south to 112 mm CL in the north due to environmental differences rather than density or effects of fishing (Gardner et al, 2006). Spatial heterogeneity in the fleet is most pronounced with longitude due to prevailing winds with fishers willing to tolerate lower catch rates on the more protected and accessible east coast (Hamon et al, 2009).…”
Section: Introductionmentioning
confidence: 89%
“…Spatial differences in growth were modelled with length transition matrices fitted to an extensive tag-recapture dataset of over 50 000 recapture records McGarvey and Feenstra, 2001;Chandrapavan et al, 2010). Egg per recruit varied spatially because of differences in growth and also because of spatial variation in size at onset of maturity (Gardner et al, 2006), although fecundity at size was constant across regions (Green et al, 2009).…”
Section: Population Dynamics Model Structurementioning
confidence: 99%